Effects of a telehealth program for wound healing promotion on the wound healing level in patients with diabetes undergoing coronary artery bypass graft surgery: A randomized controlled trial - Siriporn Sumrattana; Usavadee Asdornwised; Kessiri Wongkongkam; Kriangkrai Tantiwongkosri (Belitung Nursing Journal, 2023)
Background: Patients with diabetes undergoing coronary artery bypass graft (CABG) are at risk of delayed wound healing. The telehealth program for wound healing promotion (TPWHP) was developed to improve wound healing in patients with diabetes undergoing CABG in a university hospital. Objective: This study aimed to examine the effects of the TPWHP on the healing of the sternal wound and saphenous vein graft (SVG) donor site in patients with diabetes undergoing CABG. Methods: In this randomized controlled trial, the participants were randomly assigned to the intervention (n = 30) and control (n = 30) groups. The control group received routine nursing care, whereas the intervention group received routine nursing care along with the TPWHP, which provides education and wound monitoring using multimedia and a surgical wound care booklet and monitors the wound through the LINE application on a smartphone after hospital discharge. Data were collected from June to November 2020 at two university hospitals in Bangkok, Thailand, using the demographic and health-related data form and the Thai wound assessment inventory (WAI). Data were analyzed using the Chi-squared, Fisher’s exact, and Mann–Whitney U tests. Results: The intervention group had significantly lower mean scores—indicating favorable wound healing—for SVG donor site wound healing level than the control group on days 14–21 after surgery (p = 0.012, mean = 0.58 ± 0.54 and 1.08 ± 0.82, respectively). No significant intergroup difference was observed in terms of the sternal wound healing level (p = 0.126); however, the intervention group showed lower mean scores—indicating good wound healing—than the control group. Conclusion: The TPWHP promotes effective wound healing of the SVG donor site; however, its efficacy on sternal wound healing was uncertain. Therefore, nurses should implement the TPWHP in collaboration with a multidisciplinary team to improve wound healing after hospital discharge. Trial registration: Thai Clinical Trials Registry (TCTR20211112002)